Penerapan Metode Activity Based Costing dalam Menentukan Harga Pokok Produksi Karet PT. Sumber Djantin Sambas - Gowardy, Gowardy; Brata, Handi (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
This study aims to understand how to allocate overhead cost in rubber-processing factory of PT. Sumber Djantin Sambas using Activity-Based Costing method. Furthermore, this research also attempts to compare the allocation results of the existing costing systems in PT. Sumber Djantin Sambas with those created through Activity-Based Costing systems. To accomplish these objectives, this study applies case study method. The main sources of data come from interview transcript and cost and financial documents. This study results show that the cost of goods manufactured for product SIR 20 and compound rubber are overcosted. Betweeen these two products, SIR 20 is more overcosted. The total overcosting of these two products reaches Rp 2.749.997.488,57. Using Activity Based Costing, company can allocate the costs more accurately and reduce the distortion effect of costs which is caused by traditional overhead allocation method.